2009
DOI: 10.1007/978-3-642-03658-3_86
|View full text |Cite
|
Sign up to set email alerts
|

Interactive and Lightweight Mechanisms to Coordinate Interpersonal Privacy in Mediated Communication

Abstract: Abstract. In this paper we describe three mechanisms that enable people to coordinate their interaction needs with others in their social network. The proposed designs are based on the Privacy Grounding Model [4] that argues the need for lightweight and interactive coordination mechanisms to support the dynamic and dialectic nature of interpersonal privacy coordination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The analysis so far has shown that interruption negotiation is a dynamic process. Other authors have examined this negotiation as a collaborative effort to reach a mutual understanding about the communicative contract [67,68]. This argument is supported by the research reported in this article, to which we also contribute an account of the relevant factors that should be shared.…”
Section: General Discussion and Conclusionsupporting
confidence: 71%
“…The analysis so far has shown that interruption negotiation is a dynamic process. Other authors have examined this negotiation as a collaborative effort to reach a mutual understanding about the communicative contract [67,68]. This argument is supported by the research reported in this article, to which we also contribute an account of the relevant factors that should be shared.…”
Section: General Discussion and Conclusionsupporting
confidence: 71%